A Reflection: Translocations and Changes in Perspective - Gidena Mesfin Kebede; Susanne Meyer-Abich (Journal for Art Market Studies, 2018)
“The Story of an Ethiopian Icon” is the subtitle of an article on an article published on a website promoting the return of objects taken from Maqdala in today’s Ethiopia. Under the heading “The Treasure” it gives a summary of the history of a specific painting which is indeed fascinating. This article will follow the different stages in the reception and interpretation of this object, and explore the genealogy of the story, its sources, their dependability and the varying historiographical approaches.